2017
DOI: 10.1002/mc.22657
|View full text |Cite
|
Sign up to set email alerts
|

The miR‐200b–ZEB1 circuit regulates diverse stemness of human hepatocellular carcinoma

Abstract: Accumulating evidence suggests that human hepatocellular carcinoma (HCC) can be derived from cancer stem cells (CSCs), which contribute to tumor initiation, metastasis, chemoresistance, and recurrence. A great variety of HCC CSCs resulting in diverse clinical manifestations have been reported. However, how CSC diversity is regulated and generated remains unclear. Here we report that the miR-200b-ZEB1 circuit is closely involved with the induction and maintenance of a diverse group of CSCs. We found that miR-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 53 publications
1
27
1
Order By: Relevance
“…Here, we demonstrate that miR-200b is downregulated in HCC cells, a finding that is in agreement with previous reports. 21 , 26 In addition, our data show that miR-200b downregulation is significantly associated with shorter overall survival and shorter disease-free survival. A critical role for the aberrant expression of miR-200b in hepatocarcinogenesis is supported by our finding that miR-200b overexpression in HepG 2 cells results in suppression of cell growth and migration, and reduces CD36 expression levels, similar to knockdown of HMGB3.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Here, we demonstrate that miR-200b is downregulated in HCC cells, a finding that is in agreement with previous reports. 21 , 26 In addition, our data show that miR-200b downregulation is significantly associated with shorter overall survival and shorter disease-free survival. A critical role for the aberrant expression of miR-200b in hepatocarcinogenesis is supported by our finding that miR-200b overexpression in HepG 2 cells results in suppression of cell growth and migration, and reduces CD36 expression levels, similar to knockdown of HMGB3.…”
Section: Discussionmentioning
confidence: 55%
“…These results are in agreement with preceding reports and demonstrate significant downregulation of miR-200b in HCC. 21 , 26 We further analyzed whether there is a correlation between expression of HMGB3 and expression of miR-200b. The HMGB3 RSEM value of 10.825 from TCGA RNA-seq HCC tissues was used as the cutoff point to divide the HCC tissues into low (n = 241) and high (n = 126) HMGB3 expression groups.…”
Section: Resultsmentioning
confidence: 99%
“…Among these transcription factors, we found that ELF3-induced EMT through ZEB1 activation. ZEB1, a member of the ZEB family of transcription factors, has been reported to be overexpressed in several human cancers, including HCC 38 40 . Previous studies have shown that ZEB1 directly promotes EMT in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The expression and functions of EMT-TFs are controlled by posttranscriptional regulator miRNAs, which regulate the expression of specific proteins by binding to mRNA transcripts with complementary sequences, destabilizing it. 103 Among the best characterized miRNAs regulating the EMT program, miR-200 family (miR-141, -200a, -200b, -200c, and -429) is well known to be associated with the progression of HCC, 104,105 while miR-205 can directly inhibit EMT by targeting EMT-TFs, ZEB1, and ZEB2 proteins. 106,107 Moreover, miR-200b-ZEB1 circuit has been suggested to function as a master regulator of stemness in HCC.…”
Section: Inducer Of Cancer-stromal Cells Interactionmentioning
confidence: 99%
“…106,107 Moreover, miR-200b-ZEB1 circuit has been suggested to function as a master regulator of stemness in HCC. 104 Intriguingly, the miR-200-ZEB1-E-cadherin axis has been demonstrated to be a crucial pathway downstream of TGF-β in the EMT, while reciprocal repression between ZEB1 and the miR-200 family has recently been reported to promote the EMT and invasion in cancer cells. 108,109 Similarly, members of the miR-34 family attenuate the expression of SNAIL.…”
Section: Inducer Of Cancer-stromal Cells Interactionmentioning
confidence: 99%